The impact of Wikis as a collaborative writing tool on EFL students’ writing - Masrul Masrul; Wida Rianti (Journal of English Language Teaching and Learning (JETLE), 2026)
This study investigated the impact of wiki-based collaborative writing on EFL students’ business writing performance in a Business English Writing course at Universitas Pahlawan Tuanku Tambusai. The study employed a quasi-experimental one-group pretest–posttest design involving 100 university students. Students participated in four types of wiki-based collaborative writing activities during the treatment period. Writing performance was assessed using an analytical scoring rubric covering overall writing, content, organization, vocabulary, language use, and mechanics. The data were analyzed using descriptive statistics, ANOVA, and paired sample t-tests. The findings revealed that there were no statistically significant differences among the four wiki collaboration types, although Wiki Type 4 obtained the highest mean score. The results also showed a significant improvement in students’ overall writing performance after the wiki-based collaborative treatment. However, no significant improvement was found in the individual writing components, including content, organization, vocabulary, language use, and mechanics. These findings suggest that wiki-based collaborative writing can support students’ overall writing development and collaborative engagement, although its short-term impact on specific writing sub-skills remains limited. The study contributes to the growing body of research on digital collaborative learning in ESP and EFL writing contexts.